A pH reversibly activatable NIR photothermal/photodynamic-in-one agent integrated with renewable nanoimplants for image-guided precision phototherapy - Zhao, Xu; Zhao, Kai-Chao; Chen, Li-Jian; Liu, Yu-Shi; Liu, Jia-Lin; Yan, Xiu-Ping (Chemical science (Cambridge), 2020)
Phototherapy has great potential to revolutionize conventional therapeutic modalities. However, most phototherapeutic strategies based on multicomponent therapeutic agents generally lack tumor-specificity, resulting in asynchronous therapy and superimposed side-effects. Severe heat damage is also inevitable because of the necessity of continuous external irradiation. Here we show the design of an acid-activated and continuous external irradiation-free photothermal and photodynamic (PTT/PDT) synchronous theranostic nanoplatform for precision tumor-targeting near-infrared (NIR) image-guided therapy. pH-reversibly responsive brominated asymmetric cyanine is designed as the tumor-specific NIR PTT/PDT-in-one agent to enhance anticancer efficiency and reduce side-effects. Ultra-small NIR persistent luminescence nanoparticles are prepared as both the imaging unit and renewable nanoimplant. Biotin functionalized polyethylene glycol is introduced to endow active tumor-targeting ability and prolong blood-circulation. The developed smart platform offers merits of reversible activation, PTT/PDT synergetic enhancement, tumor targetability and continuous external irradiation-free properties, allowing autofluorescence-free image-guided phototherapy only in tumor sites. This work paves the way to developing smart theranostic nanoplatforms for precision medicine. A smart NIR photothermal/photodynamic-in-one agent integrated with renewable nanoimplants for autofluorescence- and continuous external irradiation-free image-guided precision tumor-targeting phototherapy.